(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2025)
This study examines nuclear regulation in the United Kingdom, focusing on licensing processes for land facilities supporting nuclear-powered submarines. It highlights the importance of these submarines for defense and maritime security, along with the need for specialized infrastructure to operate them safely and effectively. The study analyzes the UK’s procedures and regulations for nuclear licensing, with emphasis on regulatory bodies such as the Office for Nuclear Regulation (ONR) and the Defence Nuclear Safety Regulator (DNSR). Results discuss the classification of nuclear facilities in the UK, including those dedicated to submarines and nuclear defense, as well as the applicable standards and guidelines for licensing these facilities. It is concluded that nuclear regulation in the UK is robust and transparent, providing a solid foundation for licensing facilities supporting nuclear-powered submarines. The adoption of these standards as a reference in Brazil could significantly contribute to establishing a solid and secure regulatory framework for such facilities.